Pengelolaan Dokumen Untuk Tertib Administrasi Pelayanan Pada Posyandu Kasih Ibu XII, RW 12 Kelurahan Bojongsari, Kecamatan Bojongsari-Kota Depok - Suwandi Suwandi; Waluyo Waluyo; Harjoyo Harjoyo; Riri Oktarini; Dyas Mulyani Benazir (LPPM Universitas Pamulang, 2020)
Partners in community service activities are the Posyandu Kasih Ibu XII cadres, Bojongsari Kelurahan RW 12, Bojongsari Subdistrict, Depok City. The main problem faced by partners is the limited ability of human resources possessed by Posyandu cadres, especially related to the management of documents both pre -service, at the time of service delivery and post-service. Documents / documents / document archives have not been well organized, only relying on initiatives from cadres who are indeed composed of PKK (Family Welfare Empowerment) organizers who have concern to provide services to Posyandu activities. The method of implementing PKM activities is planned to begin by providing PKM activities. lecture and counseling to the Posyandu Kasih Ibu XII cadres in Bojongsari RW. 12. Then use the demonstration method and practice / simulation which is a follow-up activity carried out by the PKM implementers on the lecture and discussion activities that have been carried out. The results of this activity are Posyandu cadres who understand and understand and can practice document management so as to create effectiveness and efficiency of service to residents, especially toddlers, pregnant and breastfeeding mothersKeywords: Document Management, Administration, Services, Posyandu